Artificial intelligence and automation in the migration governance of international students: An accidental ethnography - Brunner, Lisa Ruth; Tao, Wei William (Journal of International Students, 2023)
Artificial intelligence (AI) and automation are newly impacting the governance of international students, a temporary resident category significant for both direct economic contributions and the formation of a ‘pool’ of potential future immigrants in many immigrant-dependent countries. This paper focuses on tensions within Canada’s education-migration (‘edugration’) system as new technologies intersect with migration regimes, which in turn relate to broader issues of security, administrative burdens, migration governance, and border imperialism. Using an Accidental Ethnography (AccE) approach drawing from practitioner-based legal research, we discuss three themes: (1) ‘bots at the gate’ and the guise of AI’s objectivity; (2) a murky international edu-tech industry; and (3) the administrative burdens of digitalized application systems. We suggest that researchers, particularly in education, can benefit from the insights of immigration practitioners who often become aware of potential trends before those less embedded in the everyday negotiation of migration governance.